Pengembangan Model Kualitas Pelayanan Jasa Pendidikan Sekolah Karakter di Jakarta - Kirana Rukmayuninda Ririh; Firda Meira Pratiwi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
This study aims to investigate the correlation of service quality to customer satisfaction, loyalty, and deployment of communication using Word of Mouth (WOM). The research was conducted at Character-based School in Jakarta, involving 84 parents as respondents. A purposive sampling method was applied. The data were collected through a survey questionnaire. The measurement was using a four-scale Likert. The analysis was supported by SEM (Structural Equation Modeling) which the tool was SmartPLS version 3.0. As results show that there were three significant relationships which between customer loyalty and Word of Mouth (0.691), service quality and customer satisfaction (0.298), also service quality and customer loyalty (0.340). It depicted that loyal customer was more significant than satisfying one. The conclusion of this study pointed out that loyalty played role in improving and maintaining a robust marketing strategy for Character-Based School. The more customer loyalty created the stronger word of mouth throughout customer.